Historical Dictionary of Chinese Cinema - Luo, Dan; Ye, Tan 1948-; Zhu, Yun (Historical Dictionaries of Literature and the Arts Series, 2024)
Historical Dictionary of Chinese Cinema, Second Edition contains a chronology, an introduction, and an extensive bibliography. The dictionary section has more than 200 cross-referenced entries on the major filmmakers, actors, and historical figures, representative cinematic productions, genre evolution, significant events and institutions.